Pengaruh Metode Pembelajaran Numbered Heads Together (Nht) Terhadap Prestasi Belajar Ditinjau Dari Keaktifan BelajarMatematika Siswa Kelas Vii Smp Negeri 1 Teras Tahun Pelajaran 2015/2016. - Elfira Widiastuti, Indriani; , Dra. Sri Sutarni, M.Pd (2017)
This study aims to find out: (1) The effect of Numbered Heads Together method and expository method on students' mathematics learning achievement, (2) The effect of students activities on students' mathematics learning achievement, (3) The effect of interaction Numbered Heads Together method and expository method, and students activities on students' mathematics learning achievement. This is an experiment with a quasi experimental design. The population of this study was all seven graders of SMP Negeri 1 Teras in the even semester of academic year 2015/2016. The sample of this study was sudents two classes, consisting 34 students for the experimental class and 34 students for the control class. The sampling technique used in this study was cluster random sampling. The Methods used for collecting the data were test, questionnaires and documentation. The data were analyzed by using analysis of variance with two different cell lines. Based on the data analysis with 5% of significant level, it can be concluded that: (1) There is an effect of Numbered Heads Together method and expository method on students' mathematics learning achievement. The students who were treated with Numbered Heads Together method in their learning process showed higher academic achievement than those who are treated with expository method, (2) There is effect of students activities on students' mathematics learning achievement. The students who have better activities showed higher academic achievement compare to those who have moderate or poor activities, (3) There is no interaction between Numbered Heads Together method and expository method, and students activities on students' mathematics learning achievement. Keyword: Expository, Learning Achievement, Numbered Heads Together, Students Activities.